2009
DOI: 10.3997/1873-0604.2009002
|View full text |Cite
|
Sign up to set email alerts
|

Trends in waterborne electrical and EM induction methods for high resolution sub‐bottom imaging

Abstract: Shallow water applications of electrical and electromagnetic geophysical methods have grown in recent years with recognition of the information these methods can provide regarding groundwater‐surface water interaction, geotechnical engineering, exploration, marine geology and other fields. In many applications, spatial variations in resistivity are useful as a proxy for variations in another bulk material property such as pore water salinity, clay content, porosity, or temperature. Applications of galvanic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…It is worth mentioning that previous shallow-water TEM studies (Butler, 2009;and references therein;Hatch et al, 2010;Mollidor et al, 2013) employed in-loop configurations with an outer transmitter loop and a smaller receiver loop or coil in the centre, while we used a single-loop configuration, which is quicker to assemble and easier to handle while navigating on the lake. We also showed that it is sensible to constrain the interpretation of the sounding data by incorporating water depth and eventually water resistivity into the inversion process as a-priori information.…”
Section: Sediment-thickness Estimation From Tem Soundingsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that previous shallow-water TEM studies (Butler, 2009;and references therein;Hatch et al, 2010;Mollidor et al, 2013) employed in-loop configurations with an outer transmitter loop and a smaller receiver loop or coil in the centre, while we used a single-loop configuration, which is quicker to assemble and easier to handle while navigating on the lake. We also showed that it is sensible to constrain the interpretation of the sounding data by incorporating water depth and eventually water resistivity into the inversion process as a-priori information.…”
Section: Sediment-thickness Estimation From Tem Soundingsmentioning
confidence: 99%
“…In particular, low-frequency echo sounders (e.g., Dondurur, 2018), also referred to as sub-bottom profilers (SBP), allow to quickly map sediment deposits of several tens of meters based on single-channel seismic data. Nevertheless, electrical-resistivity data provided by electrical resistivity tomography (e.g., Binley and Kemna, 2005) or electromagnetic soundings (e.g., Kaufman et al, 2014) can complement the mostly geometrical information obtained from reflection-seismic or sub-bottom profiling measurements (Butler, 2009). Under certain conditions such as high lake-bed reflectivity and/or low reflectivity of targeted boundaries, seismic methods may, however, provide insufficient results and therefore alternative methods are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the existing methods and recent case histories can be found in the Special Issue of Near Surface Geophysics on Waterborne Geophysics (Butler, 2009;Sambuelli and Butler, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Among the available geophysical techniques, the use of nonseismic methods with this aim has received growing attention in recent years. A detailed review on the topic can be found, for example, in the special issue of Near Surface Geophysics specifically devoted to waterborne geophysics (Butler, 2009;Sambuelli and Butler, 2009).…”
Section: Introductionmentioning
confidence: 99%